Nursing performance in an orthopedic and traumatology emergency service - Faro, Ana Cristina Mancussi e (1987)
To determine the adequary of nursing assistance to population demand, the authors developed a brief survey of the actual physical area, nursing personnel, equipament and supply of the Orthopedic and Traumatology Emergency Service where the study is been done.